Nanoporous Alumina Support Covered by Imidazole Moiety–Based Ionic Liquids: Optical Characterization and Application - Algarra-González, Manuel; López-Escalante, María Cruz; Martínez de Yuso García, María del Valle; Soto-Martín, Juan (IOAP-MDPI, 2022)
This work analyzes chemical surface and optical characteristics of a commercial nanoporous alumina structure (NPAS) as a result of surface coverage by different imidazolium-based ionic liquids (1-butyl-3-metylimidazolium hexafluorophosphate, 3-methyl-1-octylimidazolium hexafluorophosphate, or 1-ethyl-3-methylimidazolium tetrafluoroborate). Optical characteristics of the IL/NPAS samples were determined by photoluminescence (at different excitation wavelengths (from 300 nm to 400 nm), ellipsometry spectroscopy, and light transmittance/reflectance measurements for a range of wavelengths that provide information on modifications related to both visible and near-infrared regions. Chemical surface characterization of the three IL/NPAS samples was performed by X-ray photoelectron spectroscopy (XPS), which indicates almost total support coverage by the ILs. The IL/NPAS analyzed samples exhibit different photoluminescence behavior, high transparency (<85%), and a reflection maximum at wavelength ~380 nm, with slight differences depending on the IL, while the refractive index values are rather similar to those shown by the ILs. Moreover, the illuminated I–V curves (under standard conditions) of the IL/NPAS samples were also measured for determining the efficiency energy conversion to estimate their possible application as solar cells. On the other hand, a computational quantum mechanical modeling method (DFT) was used to establish the most stable bond between the ILs and the NPAS support.
Keywords: Células solares; Nanoporous alumina; Ionic liquids; Optical properties; Solar cell